Purple Corn (Zea mays indurata) Ice Cream as an Immune Booster in The Pandemic Era - Faza Saiqur Rahmah; Fitriyani Fitriyani; Lisa Aulia Zahra; Muhamad Abdulloh Umar; Muhammad Abbas Arriziq; Burhan Ma'arif (Food ScienTech Journal, 2022)
The COVID-19 pandemic has had an impact on public health. Immune resistance was a crucial factor in the pandemic era considering all diseases that arise as self-limiting diseases. Food as a source of nutrients had a vital role as an immunomodulator. As an agricultural country with food production commodities that were still massive, agricultural products are needed to develop food innovations, such as purple corn. One of the nutritional contents of purple corn was the flavonoid group in the form of anthocyanin compounds as a source of antioxidants to increase the body's immunity and prevent diseases caused by viruses, fungi, and bacteria, as well as prevent atherosclerosis, gastric damage, cholesterol, obesity, and others. Anthocyanin compounds in purple corn 70mg/100 grams. Anthocyanins in purple corn are processed into healthy food in ice cream with the product label "Purple Corn Ice Cream". This research aims to help people choose food innovations that can help them increase their immunity in the Covid-19 pandemic era. This ice cream product was formulated and has gone through several tests. The anthocyanin test results showed that the sample contained anthocyanins. The sensory test results stated that this product had a soft texture, milky smell, light purple colour, and sweet taste, so it was accepted and received a positive response from the community. Based on the total questionnaire assessment results, 88% of respondents. Purple Corn Ice Cream was expected to be a nutritious food innovation, popular with people regardless of age, practical, and durable with the content of flavonoid anthocyanin compounds in purple corn, which can improve the body's immune system during a pandemic.